City limits: sexual politics and the new urban left in 1980s Sheffield. Issue 2 (3rd April 2017) - Payling, Daisy
Abstract: In the 1980s Sheffield had a vibrant political milieu made up of labour and new social movement activists who were variously supported by a left-wing Labour-led City Council. Sheffield City Council developed their own form of local socialism which fed into the ideas of the new urban left and left-wing thinkers like Stuart Hall and his contemporaries at Marxism Today . Sheffield City Council was interested in uniting class and identity politics in a form of political renewal; however, both the Council and the city's dominant labour movement preferred to focus on material concerns. Sheffield's politics was energetic but inchoate and messy. Whilst the Council and labour movement made supportive links with peace, anti-apartheid and women's movements, certain groups were left on the outside. Uniting class and identity over gay politics proved a bridge too far. This article explores Sheffield's gay politics to show how left-wing solidarity in the city broke down. Sheffield's new urban left found its limits in the arena of gay politics.